PENDEKATAN PERUNDANG-UNDANGAN, KONSEPTUAL, DAN KASUS DALAM PENELITIAN HUKUM NORMATIF - Wiliam Kristianto; Hery Chariansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Abstract This article examines the function and integration of statutory, conceptual, and case approaches in normative legal research. Primary materials comprise constitutional provisions, legislation, and judicial decisions, supported by books and journal articles from 2020–2026. Legal interpretation, conceptual analysis, and ratio decidendi analysis are applied. The statutory approach maps validity, hierarchy, consistency, and scope; the conceptual approach constructs standards from principles and doctrines; and the case approach examines rules through legally relevant facts, reasoning, and holdings. A four-stage integration model is proposed.